2013
DOI: 10.1007/s10461-012-0404-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV Knowledge and Beliefs Among Men Who Have Sex With Men (MSM) in Buenos Aires, Argentina

Abstract: Five hundred men who have sex with men (MSM), recruited through Respondent Driven Sampling in Buenos Aires, Argentina, were interviewed in order to assess knowledge and beliefs about HIV infection. The mean proportion of HIV correct knowledge answers was 62%; however participants whose sexual partners in the prior year included women (MSM&W) had lower frequencies of correct answers than participants with no women partners. Men with previous HIV testing experience and those who were HIV positive had higher HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
5
16
0
5
Order By: Relevance
“…These findings are consistent with previous reports of scales with similar domains among GBMSM in the US (Swenson et al, 2010; Wagenaar et al, 2012; Pando, et al, 2013; Fay et al, 2011). However, SHK scores in our study sample were slightly higher than those reported by Vanable and colleagues (2011).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous reports of scales with similar domains among GBMSM in the US (Swenson et al, 2010; Wagenaar et al, 2012; Pando, et al, 2013; Fay et al, 2011). However, SHK scores in our study sample were slightly higher than those reported by Vanable and colleagues (2011).…”
Section: Discussionsupporting
confidence: 93%
“…Socioeconomic (e.g., high schooling and monthly income) and behavioral factors (e.g., number of friends or acquaintances who are gay or bisexual, having sex exclusively with men, homosexual sexual orientation, and consistent use of condom) have been associated with high knowledge 21,[24][25][26] . Factors related to healthcare services, including HIV testing and the diagnosis of sexually transmitted infections (STI), are also associated with better knowledge about HIV/AIDS 21,[25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados em outros países avaliaram o conhecimento sobre HIV, especificamente entre os HSH, e encontraram resultados relevantes que mostraram os seguintes fatores associados com o baixo conhecimento sobre HIV: menor escolaridade; idade menor que 25 anos e maior do que 50; grupo racial não branco; nunca ter realizado teste para HIV; HSH com resultado negativo para HIV; não usar preservativos na última relação sexual e menor número de parceiros sexuais 15,16,17,18,19 .…”
Section: Introductionunclassified